Effect of Eight Weeks of High-Intensity Interval Training (HIIT) on Serum Asprosin Levels and Body Composition in Overweight and Obese Men - Almasoodi, Ameer; Amirsasan, Ramin; Vakili, Javad; Khani, Mostafa; Alwawi, Hussein (International Journal of Sport Studies for Health, 2026)
Objective:  This study aimed to investigate the impact of 8 weeks of high-intensity interval training (HIIT) on serum Asprosin levels and body composition in overweight and obese men.Methods and Materials: A total of 36 overweight and obese men with a body mass index (BMI) of 25 to 34.9 aged between 30 and 35 years, were voluntarily selected and randomly assigned to either the HIIT group or a control group in a semi-experimental, pre-post study design. The HIIT intervention lasted for eight weeks, consisting of three sessions per week. Asprosin was measured using ELISA, while body composition was assessed via InBody 230 analysis. Statistical comparisons were performed using ANCOVA with significance set at α < 0.05.Findings: Following the intervention, the HIIT group exhibited significant reductions in serum asprosin levels (F = 134.06, p < 0.01), body fat percentage (F = 186.79, p < 0.01), BMI (F = 25.36, p < 0.01), lean body mass (F = 9.88, p = 0.004), and waist-to-hip ratio (F = 9.88, p < 0.01).Conclusion: These findings support the role of HIIT as an effective non-pharmacological strategy for reducing serum Asprosin levels and improving body composition in overweight and obese populations.